2017
DOI: 10.3389/fmicb.2017.02427
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Changes Induced by Infection of Cucumber (Cucumis sativus L.) with Mild and Severe Variants of Hop Stunt Viroid

Abstract: Fifteen years after transfer to hops, hop stunt viroid-grapevine (HSVd-g) was replaced by HSVd-hop (HSVd-h), a sequence variant that contains changes at five different positions. HSVd-g54 is a laboratory mutant derived from HSVd-g that differs from its progenitor by a single G to A substitution at position 54. While infection by HSVd-h induces only mild stunting in cucumber (Cucumis sativus L.), HSVd-g54 induces much more severe symptoms in this indicator host. Comparison of transcriptome profiles of cucumber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 89 publications
7
83
0
1
Order By: Relevance
“…It has been confirmed that trypsin significantly impacts on the free radical scavenging activities of flavonoids [8]. Our previous results also showed that trypsin scavenges superoxide anions (O 2 • − ) and protects cells [9].In the area of phytopathology, transcriptomic analysis has been successful used on lots of plants [10][11][12][13]. However, few of transcriptomic works have been focused on the preservation of fruits.…”
mentioning
confidence: 86%
“…It has been confirmed that trypsin significantly impacts on the free radical scavenging activities of flavonoids [8]. Our previous results also showed that trypsin scavenges superoxide anions (O 2 • − ) and protects cells [9].In the area of phytopathology, transcriptomic analysis has been successful used on lots of plants [10][11][12][13]. However, few of transcriptomic works have been focused on the preservation of fruits.…”
mentioning
confidence: 86%
“…Photosynthesis-related genes, such as the photosystem ones, can be downregulated by 522 biotic agents [114]. Furthermore, microarray gene expression studies of Arabidopsis and photosynthesis genes for weeks after infection [33,116]. This is in agreement with 530 the physiological impact of orange rust, because measures of chlorophyll content and net 531 photosynthetic rate of sugarcane leaves decrease according to susceptibility to P.…”
mentioning
confidence: 64%
“…In contrast, phenylpropanoid biosynthesis was enriched at 12 hai in 449 the compatible interaction of an apple cultivar and A. alternata [38]. Furthermore, this 450 pathway was enriched with downregulated genes in cucumber infected by a mutant of 451 hop stunt viroid-grapevine at 28 dai [33]. In sugarcane smut, tyrosine accumulation is 452 characteristically associated with phenylpropanoid biosynthesis [104].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting the advantage in the present study, we explored the early molecular changes leading to the development of chlorosis using RNA-seq analysis. Although studies have shown the transcriptome changes in virus- and viroid-infected plants (Mochizuki et al ., 2014; Xia et al ., 2017; Zheng et al ., 2017), the strength of the present study is that we could detect any changes that precede detectable chlorosis.…”
Section: Discussionmentioning
confidence: 99%